Decay of oil residues in the soil is enhanced by the presence of Spartina alterniflora, with no additional effect from microbiome manipulation - Formel, Stephen K.; Martin, Allyson M.; Pardue, John H.; Elango, Vijaikrishnah; Johnson, Kristina; Gunsch, Claudia K.; Lefèvre, Emilie; Varner, Paige M.; Kim, Yeon Ji; Bernik, Brittany M.; Van Bael, Sunshine A. (Frontiers in Soil Science, 2022)
Recent work has suggested that the phytoremediation potential of S. alterniflora may be linked to a selection by the plant for oil-degrading microbial communities in the soil, in combination with enhanced delivery of oxygen and plant enzymes to the soil. In salt marshes, where the soil is saline and hypoxic, this relationship may be enhanced as plants in extreme environments have been found to be especially dependent on their microbiome for resilience to stress and to respond to toxins in the soil. Optimizing methods for restoration of oiled salt marshes would be especially meaningful in the Gulf of Mexico, where there is a persistently high threat of petroleum contamination. One favorable strategy for restoration of oiled sites might include planting S. alterniflora with a microbiome that has been pre-selected for an oiled environment. We examined this strategy with a two-year greenhouse experiment and found that planting S. alterniflora in an oiled environment enhances decomposition of oil residues without a clear negative impact on plant growth. Manipulation of the S. alterniflora microbiome through soil inoculation and through exposure to oil residues, elicited a detectable response of soil prokaryote communities to the presence of oil, while only demonstrating an analogous response in fungal communities in the plant roots and leaves. Yet, manipulation of the plant microbiome did not change plant morphology or relative decomposition of polycyclic aromatic hydrocarbons (PAHs) in the soil. Therefore, despite evident relationships between the plant, microbes, and oil, manipulation of the microbiome may not be a worthwhile addition to S. alterniflora phytoremediation strategies. Nevertheless, our work adds support for replanting S. alterniflora in oiled salt marshes as an effective strategy for reducing oil residues in salt marshes, in addition to the re-vegetation and erosion reduction benefits demonstrated by others.